2016
DOI: 10.3389/fimmu.2016.00435
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Dendritic Cell Maturation and Activation by a Potential Adjuvant, 2-Hydroxypropyl-β-Cyclodextrin

Abstract: 2-Hydroxypropyl-β-cyclodextrin (HP-β-CD) is a chemically modified cyclic oligosaccharide produced from starch that is commonly used as an excipient. Although HP-β-CD has been suggested as a potential adjuvant for vaccines, its immunological properties and mechanism of action have yet to be characterized. In the present study, we investigated the maturation and activation of human dendritic cells (DCs) treated with HP-β-CD. We found that DCs stimulated with HP-β-CD exhibited a remarkable upregulation of costimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 43 publications
0
23
0
Order By: Relevance
“…HPβCD, already approved as an excipient for various oral medicines and a few injectable ones, was chosen for its excellent tolerability. The synergic effect of HPβCD with immunoglobulins was proven by several previous in vivo studies with mice and macaques, which demonstrated that HPβCD brings a 30% increase in the production of antibodies and that it further induces the production of a subclass of immune cells responsible for long-term immune 'memory'; that is, long-term immunization against the virus [44,45]. It was also demonstrated that the effect of immunization occurs not only at the nasal mucosa, the site of administration, but that it is systemic, spreading throughout the entire body to convey strong immunity to the virus [46].…”
Section: Influenza Treatment and Preventionmentioning
confidence: 97%
“…HPβCD, already approved as an excipient for various oral medicines and a few injectable ones, was chosen for its excellent tolerability. The synergic effect of HPβCD with immunoglobulins was proven by several previous in vivo studies with mice and macaques, which demonstrated that HPβCD brings a 30% increase in the production of antibodies and that it further induces the production of a subclass of immune cells responsible for long-term immune 'memory'; that is, long-term immunization against the virus [44,45]. It was also demonstrated that the effect of immunization occurs not only at the nasal mucosa, the site of administration, but that it is systemic, spreading throughout the entire body to convey strong immunity to the virus [46].…”
Section: Influenza Treatment and Preventionmentioning
confidence: 97%
“…A common influenza vaccine containing 30% of HP-β-CD as adjuvant increased in the production of antibodies and produced a 100% survival rate in mice challenged with a lethal dose of influenza virus. The response produced by the vaccine takes place in every part of the body and does not remain localised at the administration site (Kim et al, 2016). It was also found that intranasal or subcutaneous administration of HP-β-CD increased the immunogenicity of influenza vaccines.…”
Section: Sentinels To Prevent Invasions: Cyclodextrins In Antiviral Vmentioning
confidence: 99%
“…HP-β-CD predominantly induced IgG1 but not IgG2, indicating preferential enhancement of Th2 responses rather than Th1 responses. Type 2 T-helper (Th2) cell response, enhances antigen (vaccine)-specific antibody titers, maintains a longer immune response and induces the maturation of dendritic cells vital for a long lasting effective immune response (Kim et al, 2016;Onishi et al, 2015). HP-β-CD was selected because it has proved to be highly biocompatible.…”
Section: Sentinels To Prevent Invasions: Cyclodextrins In Antiviral Vmentioning
confidence: 99%
“…In Japan, some researchers have been evaluating the first CD-adjuvanted vaccine in history, in this case against the influenza virus [ 95 ]. The vaccine uses CDs as adjuvant because of its ability to enhance the production of antibodies (by nearly 30%) and to induce dendritic cell maturation [ 96 , 97 ].…”
Section: Cyclodextrins As Active Drugsmentioning
confidence: 99%